Parâmetros para justiciabilidade do direito social à saúde: o caso do estado do Pará - FERREIRA, Gabriela de Cássia Moreira Abreu (Universidade Federal do Pará, 2015)
From the health care judicialization debate and their budgetary and public policies planning impacts, the research works on the assumption that the Judiciary should seek rational criteria in this kind of demand, proposing parameters for this task; also seeking to restore the balance between individual and collective aspects of health rights. Therefore, a constitutional and health law approach is presented, under the evidence-based medicine paradigm. The Brazil Federal Supreme Court jurisprudence on health social right is exposed and systematized, emphasizing the Public Hearing held in 2009 in this Court. Seeking to understand how and if this latest debate found echoes in regional and local reality, Pará State Court of Justice cases, tried between 2008 and 2011, were searched and compared with the previous analysed Federal Supreme Court jurisprudence; also exposing the demands’ characteristics from the following criteria: author species, legal representation, disease, applicants’ profile, demand results (and others), as well as the main arguments presented by the authors, defendants and judges. From our survey, specific health right justiciability parameters are proposed, influenced by Ronald Dworkin’s law as integrity theoretical framework, restoring the integration between public subjective right and collective right, as complementary nature to the right to health.